Retinal Electrophysiology Is a Viable Preclinical Biomarker for Drug Penetrance into the Central Nervous System - Jason Charng; Zheng He; Algis J. Vingrys; Rebecca L. Fish; Rachel Gurrell; Bang V. Bui; Christine T. Nguyen (Journal of Ophthalmology)
Objective. To examine whether retinal electrophysiology is a useful surrogate marker of drug penetrance into the central nervous system (CNS). Materials and Methods. Brain and retinal electrophysiology were assessed with full-field visually evoked potentials and electroretinograms in conscious and anaesthetised rats following systemic or local administrations of centrally penetrant (muscimol) or nonpenetrant (isoguvacine) compounds. Results. Local injections into the eye/brain bypassed the blood neural barriers and produced changes in retinal/brain responses for both drugs. In conscious animals, systemic administration of muscimol resulted in retinal and brain biopotential changes, whereas systemic delivery of isoguvacine did not. General anaesthesia confounded these outcomes. Conclusions. Retinal electrophysiology, when recorded in conscious animals, shows promise as a viable biomarker of drug penetration into the CNS. In contrast, when conducted under anaesthetised conditions confounds can be induced in both cortical and retinal electrophysiological recordings.